Development of Group Guidance Manual Book Based on Experiential Learning Model to Enhance Career Adaptability of Vocational School Students - Kristiyorini, Yuana; Muslihati, Muslihati; Indreswari, Henny; Wu, (citeus, 2025)
Career adaptability is the ability of individuals to prepare themselves to complete various predicted tasks and engage in work roles, as well as to handle unexpected problems that arise due to transitions in the workplace. This research and development aims to develop a guidance handbook using an experiential learning model to enhance the career adaptability of vocational school students. This research is a research and development using the ADDIE model (analysis, design, development, implementation, and evaluation). The results of the expert test assessment and prospective users applied inter-rater agreement data analysis. Furthermore, the product effectiveness test was analyzed using the Wilcoxon signed-rank test method. Based on the validation of material experts, media, and prospective users, as well as the effectiveness test for students, it can be concluded that the guide is very high in validity according to the aspect of acceptability. Thus, it can be concluded that the guidance handbook using an experiential learning model to enhance the career adaptability of vocational school students is suitable for use.